2015
DOI: 10.1177/1071100715587045
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Outcomes of Uncomplicated Primary Open Ankle Arthrodesis

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 28 publications
(33 reference statements)
6
59
7
Order By: Relevance
“…More investigation is necessary to determine if rhBMP-2 has a role in hindfoot and ankle fusion surgery. Previous arthrodesis of the adjacent joint is a risk factor for nonunion of the tibiotalar joint (with a previously fused subtalar joint) [7] or of the subtalar joint (with a previously fused tibiotalar joint) [12,26]. Easley et al [11], whose study included only patients who underwent revision arthrodesis, reported a union rate that was comparable to the rate in our patients.…”
Section: Discussionsupporting
confidence: 72%
“…More investigation is necessary to determine if rhBMP-2 has a role in hindfoot and ankle fusion surgery. Previous arthrodesis of the adjacent joint is a risk factor for nonunion of the tibiotalar joint (with a previously fused subtalar joint) [7] or of the subtalar joint (with a previously fused tibiotalar joint) [12,26]. Easley et al [11], whose study included only patients who underwent revision arthrodesis, reported a union rate that was comparable to the rate in our patients.…”
Section: Discussionsupporting
confidence: 72%
“…Generating compression across a fracture surface stabilises the fracture site by increasing the frictional contact between the opposed bone ends to neutralize micromotion and withstand bending, shearing & torsional stressors (Ashhurst 1986; Kaspar et al 2005). Rigid compression fixations with minimal interfragmentary movement as such, has been shown to be beneficial for primary bone healing (Chalayon et al 2015; Latt et al 2015; Mirhadi et al 2013). Promoting direct bone healing is especially critical to achieve successful union of ankle arthrodeses due to the lack of periosteal or endosteal joint coverage to facilitate secondary healing via callus formation (Kildow et al 2016; Yakacki et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Non-union of ankle arthrodesis in humans have been described to be between 9 and 17 %, with bone resorption attributed to be a major contributing factor especially in static fixation constructs (Chalayon et al 2015; Latt et al 2015). This is supported by a study conducted by Yakacki et al (2010) that demonstrated the inability of static internal fixations to provide sustained compression in the face of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bone graft with internal or external compression will enhance the likelihood of a successful arthrodesis [31, 3537]. In studies ranging in size from 12 to 101 patients, rates of successful primary ankle fusion of 80–100% have been reported.…”
Section: Discussionmentioning
confidence: 99%